Direct seeding rice: A solution to improve establishment of rice under unpredictable climate condition - Susanti Zuziana; Sakai Chikaya; Tafakresnanto Chendy; Sasmita Priatna; Abdurachman Haris (BIO Web of Conferences)
Swampy is identified as a potential areas to boost national rice production, however, Fe exposure and lack of labour are some of main obstacles to get high yield of rice. Specific land preparation, puddling and levelling without exposing active Fe is required to maintain high yield. A field experiment aims to examine the effectiveness of perfect land levelling to increase yield under direct seeding method. The trial was arranged in large areas, each treatment was set in 0.5 ha, with 5 replications in 2021 dry-season in Central Kalimantan. The treatments were combination of land preparation and establishment system with direct seeding rice (DSR) or transplanting (TRP). The results showed that land levelling used the farming bulldozer improved the number of productive tillers lead to higher grain yield compare to that of hand tractor. Highest grain yield was produced in FB-TRP (land preparation done by Farming Bulldozer in combination with transplanting) at average 3326 kg/ha, followed by HT-TRP (Hand Tractor-Transplanting) at 3064 kg/ha. Whereas FB-DSR yielded at 2146 and FB-TRP at 1778 kg/ha. Good land levelling had greater effect on the seed germination and increase the number of tiller by 17.6% under direct seeding with farming bulldozer compare to hand tractor.